1997
DOI: 10.1007/bf02464088
|View full text |Cite
|
Sign up to set email alerts
|

Zaragozic acids production from discomycetes

Abstract: In search for new zaragozic acids and their derivatives that are potent inhibitors of squalene synthase, discomycetes of the order Leotiales were cultured and their fermentation broth was assayed, Three strains in 2 unidentified species of Mollisia were found to produce zaragozic acid D3 and three new analogs (F-lO863s), Fermentative production, productivity of F-10863s and mycological characteristics of the producers are described. Discomycetes are expected to be a biological resource providing novel bioactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Anke (1993, 1995) were among the pioneers in utilizing Helotiales and discovered a series of chlorinated metabolites. Our attempts succeeded in the discovery of various enzyme inhibitors, such as squalene synthase (Hosoya et al, 1997;, sphingomyelinase (Tanaka, Nara, Suzuki-Kongai, Hosoya, & Ogita, 1997;Nara, Tanaka, Hosoya, Suzuki-Konagai, & Ogita, 1999), sphigosine kinase (Kono, Tanaka, Ogita, Hosoya, & Kohama, 2000;Kono et al, 2001), testosterone reductase , antibacterials (Matsumoto, Hosoya, & Shigemori, 2010;Matsumoto, Hosoya, Tomoda, Shiro, & Shigemori, 2011;Tanabe et al, 2015;Kawashima, Hosoya, Tomoda, Kita, & Shigemori, 2018), plant growth regulation factors (Tanabe, Matsumoto, Hosoya, Sato, & Shigemori, 2013), and antifungals (Ohyama et al, 2002).…”
Section: Discovery Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Anke (1993, 1995) were among the pioneers in utilizing Helotiales and discovered a series of chlorinated metabolites. Our attempts succeeded in the discovery of various enzyme inhibitors, such as squalene synthase (Hosoya et al, 1997;, sphingomyelinase (Tanaka, Nara, Suzuki-Kongai, Hosoya, & Ogita, 1997;Nara, Tanaka, Hosoya, Suzuki-Konagai, & Ogita, 1999), sphigosine kinase (Kono, Tanaka, Ogita, Hosoya, & Kohama, 2000;Kono et al, 2001), testosterone reductase , antibacterials (Matsumoto, Hosoya, & Shigemori, 2010;Matsumoto, Hosoya, Tomoda, Shiro, & Shigemori, 2011;Tanabe et al, 2015;Kawashima, Hosoya, Tomoda, Kita, & Shigemori, 2018), plant growth regulation factors (Tanabe, Matsumoto, Hosoya, Sato, & Shigemori, 2013), and antifungals (Ohyama et al, 2002).…”
Section: Discovery Researchmentioning
confidence: 99%
“… Otani (1989) enumerated the Japanese mycobiota of Discomycetes , a taxon no longer used but still practical in the modern taxonomy, and enumerated 77 genera with 214 species in the order. Through our exploration and enumeration, we added 57 newly documented taxa in Japan, and 30 new taxa, including 2 genera ( Otani, Hosoya, & Furuya, 1991 ; Hosoya et al, 1993 ; Kubono & Hosoya, 1994 ; Hosoya & Otani 1995 , 1997a , 1997b , 1997c ; Hosoya & Harada 1999 ; Hosoya, 2000 , 2002 , 2004 , 2005 , 2009 ; Ono & Hosoya, 2001 ; Tanaka & Hosoya, 2001 ; Hosoya & Huhtinen 2002 ; Narumi-Saito, Hosoya, Sano, & Harada, 2006 ; Hosoya et al, 2010a , 2010c , 2011 ; Hosoya, Sung, Han, & Shin, 2010d ; Han, Hosoya, & Shin, 2011 ; Hosoya et al, 2012 ; Hosoya, Hosaka, Saito, Degawa, & Suzuki, 2013a ; Hosoya et al, 2013b ; Hosoya, Saito, & Sasagawa, 2013c ; Zhao, Hosoya, Shirouzu, Kakishima, & Yamaoka, 2013 ; Han et al, 2014a ; Hosoya, Zhao, & Degawa, 2014 ; Zhao & Hosoya, 2014 , 2015 ; Degawa et al, 2015 ; Gross, Hosoya, Zhao, & Baral, 2015 ; Hosoya & Zhao, 2016 ; Itagaki, Nakamura, & Hosoya, 2019 ; Tochihara & Hosoya, 2019 ). These included new species, new genera of both sexual and asexual states, now being merged under single names (some examples are presented in Fig.…”
Section: Systematicsmentioning
confidence: 99%
“…Pneumocandins, taxol, and zaragonic acids, which are known to be useful bioactive compounds, are isolated from plant pathogenic fungi and endophytes (Hosoya et al, 1997;Schwartz et al, 1992;Strobel et al, 1996). As a result, it was shown that plant-inhabiting fungi are useful biological resources in the exploratory search for secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Several new bioactive substances, including scyphostatin [1] and F-10863s [2,3], which have enzyme inhibition activity, have been isolated from fungi of the order Leotiales (Discomycetes). Nevertheless, the members of it have been underutilized for microbial screening [4].…”
mentioning
confidence: 99%